Doubled visions: reflexivity, intermediality and co-creation in Clouzot's The Mystery of Picasso and von Trier's and Leth's The Five Obstructions. Issue 4 (1st October 2020) - Yacavone, Daniel
ABSTRACT: Henri-George Clouzot's The Mystery of Picasso (1956) and Lars von Trier's and Jørgen Leth's The Five Obstructions (2003) are celebrated experimental documentaries on the creative process in the visual arts and cinema made (or co-made) by renowned narrative film auteurs. Ludic exercises in on-and off-screen cinematic co-creation, together they foreground creativity and its constraints; artistic style and authorship; and filmmaking as simultaneously a means of personal expression and a collaborative enterprise. The main concerns of this article, both films are also marked by an overlapping self-reflexivity, intermediality, and formal hybridity, rooted in their innovative incorporation –or nesting– of pre-existing and in-progress art works (films, paintings, drawings). Focused on multiple forms of reflexivity and a distinctly process-based incorporation of works-within-the-work, juxtaposition of the films sheds new light on these dynamics generally, as well as on the styles and careers of Clouzot and Picasso, Leth and von Trier.